2013
DOI: 10.1103/physrevd.87.023001
|View full text |Cite
|
Sign up to set email alerts
|

Quark-hybrid matter in the cores of massive neutron stars

Abstract: Using a nonlocal extension of the SU(3) Nambu-Jona Lasinio model, which reproduces several of the key features of Quantum Chromodynamics, we show that mixed phases of deconfined quarks and confined hadrons (quark-hybrid matter) may exist in the cores of neutron stars as massive as around 2.1 M⊙. The radii of these objects are found to be in the canonical range of ∼ 12 − 13 km. According to our study, the transition to pure quark matter does not occur in stable neutron stars, but is shifted to neutron stars whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(83 citation statements)
references
References 37 publications
(65 reference statements)
3
80
0
Order By: Relevance
“…We have found that hybrid star configurations reaching or even exceeding the 2M ⊙ mass constraint have cores comprised of a mixed phase of quarks and hadrons. This conclusion is similar to the one drawn when promoting the local charge neutrality condition to a global one via Gibbs construction [20].…”
Section: Discussionsupporting
confidence: 71%
“…We have found that hybrid star configurations reaching or even exceeding the 2M ⊙ mass constraint have cores comprised of a mixed phase of quarks and hadrons. This conclusion is similar to the one drawn when promoting the local charge neutrality condition to a global one via Gibbs construction [20].…”
Section: Discussionsupporting
confidence: 71%
“…[79] using a model that combines a relativistic mean field (RMF) equation of state for the hadronic sector with a non-local PNJL model for quark matter. While the non-local effective interaction between quarks does not make much of a difference compared to the local couplings used in the present work, it should be noted that RMF-based equations of state usually fail to satisfy at least one of the EoS criteria, namely the requirement of consistency with the most advanced many-body calculations of neutron matter [12,16].…”
Section: Hadron-quark First-order Phase Transitionmentioning
confidence: 99%
“…The hadron-quark phase transition is one of the most concerned topics, and so far it is still controversial whether quarks can appear in cold neutron star [34][35][36][37][38]. It is also an important topic in heavy-ion collisions, and related experiments at medium and high densities will be performed in the near future on the updated facilities of NICA at JINR-Dubna and FAIR at GSI-Darmstadt.…”
Section: Introductionmentioning
confidence: 99%